Exploring Narrative Warfare as a Tool of Psychological Influence in Contemporary Geopolitics - Joy Mukherjee (UIN Sunan Gunung Djati, 2025)
In the era of information saturation and hybrid warfare, narrative warfare has emerged as a potent psychological tool in shaping perceptions, influencing behaviours, and manipulating geopolitical outcomes. This qualitative research explores how states and non-state actors deploy narrative warfare to assert ideological dominance, undermine adversaries, and control public consciousness. Drawing on primary and secondary sources-ranging from state propaganda, disinformation campaigns, and digital storytelling-the paper investigates the use of curated narratives in recent geopolitical conflicts, such as the Russia-Ukraine war, China’s global media expansion, and the U.S. information operations in the Middle East. Using a constructivist framework and thematic analysis, this study reveals the mechanisms through which narratives alter belief systems, foster nationalistic sentiments, and polarize global discourse. Key themes include the weaponization of history, emotional appeal, enemy construction, and mythmaking. The paper argues that narrative warfare represents a subtle yet powerful extension of psychological influence, where control over meaning becomes as critical as control over territory. Ultimately, the research underscores the urgent need for geopolitical literacy, media resilience, and counter-narrative strategies in an increasingly narrative-driven global order.